Active Surveillance for Localized Prostate Cancer A New Paradigm for Clinical Management (Current Clinical Urology,, 2018)
This fully updated and revised new edition provides a comprehensive, state-of-the art review of this field, and will serve as a valuable resource for clinicians, surgeons and researchers with an interest in prostate cancer. The book reviews new data about molecular characteristics of the disease, profiles the new grading system for prostate cancer introduced in 2015, and provides new perspectives about imaging of prostate cancer, as well as the role of targeted biopsies. The text summarizes the role of biomarkers and MRI in patient selection and management and details the world wide results of active surveillance. Specific chapters address communication and ethical issues, QOL outcomes, economic aspects, and psycho-social aspects of surveillance. The role of focal therapy for low risk disease is summarized, and the data supporting preventive interventions during surveillance reviewed. This text will serve as a very useful resource for physicians and researchers dealing with, and interested in this common malignancy, as it provides a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts. .